OP89 Use of advance care directives for individuals with dementia living in residential accommodation: a descriptive survey. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Masukwedza, V; Trynor, V; Halcomb, E; Smyth, E
Abstract : Background: End-of-life decision-making for individuals with dementia needs to be addressed because as dementia progresses, their capacity to make decisions about their health care, living arrangements and end-of-life care changes. Advance care directives (ACDs) provide an opportunity for individuals with dementia to communicate their wishes, about these important issues. Aim: The aim of this study was to understand how Australian registered nurses (RNs) use ACDs for individuals with dementia living in residential aged accommodation. Methods: Two hundred and thirty eight RNs working in Australian residential aged care accommodation were recruited via social media, professional organisations and organisations providing residential accommodation. Respondents completed an online survey delivered via Survey Monkey. Findings: 59.7% of respondents reported commencing discussions around ACDs within the first month of individuals living with a dementia relocating to residential accommodation. However, 42.4% never or rarely completed ACDs. Only 59.3% stated that ACDs for individuals with dementia were always or often regularly reviewed. 53.8% identified that ACDs were always adhered to when an individual's circumstances changed. 62.6% felt that understanding amongst families about ACDs was sometimes, or often, a barrier to using ACDs. Conclusion: The implementation of ACDs in Australian residential accommodation for those living with dementia remains sub-optimal. The study has demonstrated that ACD documentation and policies describing how they should be used exist; but gaps remain around the practical implementation of ACDs. Strategies to promote communication and collaboration between residential facilities, general practitioners and carers/families could also assist in providing cohesive, high quality care.